Glycocalyx Breakdown Is Associated With Severe Disease and Fatal Outcome in Plasmodium falciparum Malaria. (12th February 2019) - Yeo, Tsin W; Weinberg, J Brice; Lampah, Daniel A; Kenangalem, Enny; Bush, Peggy; Chen, Youwei; Price, Richard N; Young, Sarah; Zhang, Hao Y; Millington, David; Granger, Donald L; Anstey, Nicholas M
Abstract: Background: Interactions between the endothelium and infected erythrocytes play a major role in the pathogenesis of falciparum malaria, with microvascular dysfunction and parasite sequestration associated with worsening outcomes. The glycocalyx is a carbohydrate-rich layer that lines the endothelium, with multiple roles in vascular homeostasis. The role of the glycocalyx in falciparum malaria and the association with disease severity has not been investigated. Methods: We prospectively enrolled Indonesian inpatients (aged ≥18 years) with severe (SM) or moderately severe (MSM) falciparum malaria, as defined by World Health Organization criteria, and healthy controls (HCs). On enrollment, blood and urine samples were collected concurrently with measurements of vascular nitric oxide (NO) bioavailability. Urine was assayed for glycocalyx breakdown products (glycosaminoglycans) using a dimethylmethylene blue (GAG-DMMB) and liquid chromatography-tandem mass spectrometry (GAG-MS) assay. Results: A total of 129 patients (SM = 43, MSM = 57, HC=29) were recruited. GAG-DMMB and GAG-MS (g/mol creatinine) were increased in SM (mean, 95% confidence interval: 3.98, 2.44–5.53 and 6.82, 5.19–8.44) compared to MSM patients (1.78, 1.27–2.29 and 4.87, 4.27–5.46) and HCs (0.22, 0.06–0.37 and 1.24, 0.89–1.59; P < 0.001). In SM patients, GAG-DMMB and GAG-MS were increased in those with a fatal outcome (n = 3; median, interquartile range: 6.72, 3.80–27.87 and 12.15, 7.88–17.20) compared to survivors (n = 39; 3.10, 0.46–4.5 and 4.64, 2.02–15.20; P = 0.03). Glycocalyx degradation was significantly associated with parasite biomass in both MSM (r = 0.48, GAG-DMMB and r = 0.43, GAG-MS; P < 0.001) and SM patients (r = 0.47, P = 0.002 and r = 0.33, P = 0.04) and inversely associated with endothelial NO bioavailability. Conclusions: Increased endothelial glycocalyx breakdown is associated with severe disease and a fatal outcome in adults with falciparum malaria. Abstract : In a prospective study of Indonesian adults with falciparum malaria, glycocalyx breakdown was associated with impaired endothelial nitric oxide bioavailability, increased parasite biomass, endothelial activation, disease severity, and risk of death.